ADAPTASI HUNIAN LERENGAN DI KAMPUNG PELANGI KOTA SEMARANG - Ardiyanto, Antonius (UNISSULA Semarang, 2024)
ABSTRACTThe sloping land in Kampung Pelangi Semarang has unique characteristics, with gradients ranging from gentle to steep, posing challenges for creating residential areas that are safe from landslides. This research aims to understand how housing forms adapt to occupy sloping land with gradients from gentle to steep in Kampung Pelangi. The method used in this research is a descriptive qualitative approach with samples consisting of residential buildings on the slopes of Kampung Pelangi. The findings of this research show that the spatial arrangement of housing in Kampung Pelangi adapts to the slope conditions, resulting in both wide and narrow flat spaces. The boundaries of the residential areas use retaining walls to enhance land stability and serve as the foundation for the outer walls of the buildings. There are private spaces such as terraces that are utilized as circulation paths between residences in Kampung Pelangi.Key words: Residential, sloping land, adaptation, structureABSTRAKLahan berlereng di Kampung Pelangi Semarang memiliki karakteristik yang unik, dengan kemiringan lahan dari landai sampai curam akan menjadi tantangan menjadi area hunian, yang aman dari longsor. Penelitian ini bertujuan untuk mengetahui bagaimana adaptasi bentuk hunian dalam menempati lahan lerengan dengan kemiringan yang landai sampai curam di Kampung Pelangi. Metode yang digunakan dalam penelitian ini menggunakan pendekatan kualitatif deskriptif dengan sampel adalah bangunan hunian dilerengan Kampung Pelangi. Temuan dari penelitian ini tata ruang hunian di Kampung Pelangi beradaptasi dengan kondisi lerengan sehingga ada yang memiliki ruang datar yang lebar maupun yang sempit. Batas lahan hunian menggunakan talud atau dinding penahan tanah dipakai untuk memperkuat stabilitas lahan sekaligus dipakai sebagai pondasi bangunan pada dinding luar bangunan. Terdapat ruang yang bersifat privat seperti teras dimanfaatkan sebagai jalur sirkulasi jalan antar hunian di Kampung Pelangi.Kata kunci: Hunian, adaptasi, lerengan, struktur